The sex differences in diseases progression and prognosis among persons with HIV and HBV coinfection - Rongrong Yang; Qianhui Chen; Fangzhou Jiao; Xingxia Yu; Yong Xiong (Scientific Reports)
Abstract To investigate sex differences in liver disease development and prognosis in individuals with HIV and HBV co-infection. This study comprised 752 HIV/HBV co-infected people who were diagnosed with HIV and started on combination antiretroviral therapy (cART) between January 31st, 2015 and January 31st, 2023. Their clinical data, including CD4+ T lymphocyte counts, HBV-DNA, and FIB-4 scores, were tracked once a year. The prognosis was determined during the long-term surveillance period. Risk factors related with the progression of liver diseases were included in both univariable and multivariable logistic regression. Then, sex differences in CD4+ T lymphocyte counts, HBV-DNA, FIB-4 scores, changes in liver fibrosis levels, and prognosis were investigated. Multivariable logistic regression analysis identified male as an independent risk factor for liver disease progression. Compared to the male group, the female group had a significantly greater decline of HBV DNA levels at years 1, 2, 3, 3–5, and > 5 post-cART. At each assessment point, the female group showed a significantly greater rise in CD4+ T lymphocyte counts than the male group based on their respective baseline values. Furthermore, females had greater CD4+ T lymphocyte counts and a lower prevalence of liver cirrhosis than males throughout the study period. Compared to female, higher incidence of end-stage-liver disease (1.190/100 person-years vs 0.714/100 person-years), higher all-cause mortality (0.440/100 person-years vs 0.148/100 person-years) and higher mortality associated with end-stage-liver diseases (0.273/100 person-years vs 0.074/100 person-years) were found in male. Among individuals with HIV and HBV coinfection, males had a worse therapeutic effect of HBV-active therapy and poorer prognosis than females.